2022
DOI: 10.1371/journal.pone.0263587
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR) are more prominent in retinal artery occlusion (RAO) compared to retinal vein occlusion (RVO)

Abstract: Aim To evaluate the association between the value of neutrophil to lymphocyte ratio (NLR), platelet to lymphocyte ratio (PLR), monocyte to high-density lipoprotein ratio (MHR) and the development of retinal artery occlusion (RAO) and retinal vein occlusion (RVO). Methods This retrospective study assessed 41 RAO, 50 RVO and 50 control (age and gender matched senile cataract) participants. The NLR, PLR and MHR parameters of patients’ peripheral blood were analyzed. A receiver operating characteristics (ROC) cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…Some authors have reported a significant association between higher PLR and RVO, suggesting that it could be used as a prediction biomarker for identifying the risk of RVO. [ 12 , 26 ] Higher pretreatment PLR levels are a significant prognostic factor in patients with macular edema secondary to RVO following anti-VEGF treatment and significantly associated with an effective visual outcome. [ 27 , 28 ] In the current study, PLR has the lowest AUC value (0.630) in predicting RVO according to ROC curve analysis and showed the lowest sensitivity among inflammatory indicators.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some authors have reported a significant association between higher PLR and RVO, suggesting that it could be used as a prediction biomarker for identifying the risk of RVO. [ 12 , 26 ] Higher pretreatment PLR levels are a significant prognostic factor in patients with macular edema secondary to RVO following anti-VEGF treatment and significantly associated with an effective visual outcome. [ 27 , 28 ] In the current study, PLR has the lowest AUC value (0.630) in predicting RVO according to ROC curve analysis and showed the lowest sensitivity among inflammatory indicators.…”
Section: Discussionmentioning
confidence: 99%
“…In many pathologies based on inflammation, inflammatory indicators obtained from peripheral blood are now used as prognostic markers and progression predictors of many diseases, including RVO. [7][8][9][10][11][12][13][14][15] This is the first study to evaluate systemic inflammation response index (SIRI) and monocyte-to-lymphocyte ratio (MLR) in elderly patients with RVO. The present study aims to determine the potential associations and the predictive value of inflammatory indicators such as the SIRI, neutrophil-tolymphocyte ratio (NLR), MLR, platelet-to-lymphocyte ratio (PLR), systemic immune-inflammation index (SII), and other hematologic parameter characteristics in patients with RVO.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[8][9][10][11][12][13] Furthermore, these serum inflammatory biomarkers have been linked to the onset of ocular disorders such as dry eye disease, keratoconus, retinal vein occlusion, and retinal artery occlusion. [14][15][16][17][18] While the role of NLR and PLR has been previously explored in iERM, [19,20] the current study aimed to evaluate the probable relationship between MLR, NLR, and PLR serum inflammatory biomarkers in participants with iERM.…”
Section: Introductionmentioning
confidence: 99%
“…As an inexpensive and convenient marker of in ammation, monocyte to lymphocyte ratio (MLR), neutrophil to lymphocytes ratio (NLR) and platelet to lymphocyte ratio (PLR) have gained increasing attention in various disorders such as multiple types of cancers, COVID-19, Alzheimer disease and acute coronary disease (CAD) [8][9][10][11][12][13]. Furthermore, these serum in ammatory biomarkers have been linked to the onset of ocular disorders such as dry eye disease (DED), keratoconus, retinal vein occlusion (RVO) and central retinal artery occlusions (CRVO) Page 3/12 [14][15][16][17][18]. While the role of NLR and PLR have been previously explored in iERM [19,20], the current study aimed to evaluate the probable relationship between MLR, NLR and PLR serum in ammatory biomarkers in participants with iERM.…”
Section: Introductionmentioning
confidence: 99%